Efektivitas Permainan sebagai Metode Pelatihan Teknik Lompat Jauh - Muh. Yasa (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Learning long jump techniques in sports coaching education requires training methods that are not only effective but also capable of increasing athlete motivation and engagement. One emerging approach is the use of games as a training method. This literature review aims to analyze the effectiveness of a game-based approach in improving long jump technical skills, including the run-up, take-off, airborne, and landing. A review of several studies conducted between 2018 and 2024 indicates that game-based methods significantly improve motor coordination, explosive leg muscle power, and rhythmic movement ability compared to conventional training approaches. This approach has also been shown to increase self-confidence, training enthusiasm, and concentration in both beginner and elementary and secondary school athletes. Furthermore, game-based learning is considered more adaptive to the psychological development of young athletes because it provides a fun, competitive, and non-monotonous atmosphere. This study concludes that game-based training methods are highly relevant for application in the context of sports coaching education, particularly in long jump instruction, as they can improve technical performance, motivation, and the learning experience of athletes. Further research is recommended to develop more structured game models and analyze their impact on improving the performance of advanced athletes.